2011
DOI: 10.2172/1027191
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Waste Form Development and Optimization—Cast Stone

Abstract: Washington River Protection Solutions is considering the design and construction of a Solidification Treatment Unit (STU) for the Effluent Treatment Facility (ETF) at the Hanford Site. The ETF is a Resource Conservation and Recovery Act-permitted, multi-waste, treatment and storage unit that can accept dangerous, low-level, and mixed wastewaters for treatment. The STU needs to be operational by 2018 to receive secondary liquid wastes generated during operation of the Hanford Tank Waste Treatment and Immobiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(77 citation statements)
references
References 59 publications
3
74
0
Order By: Relevance
“…Several review articles (Mattus and Gilliam 1994;Langton et al 2001;Milestone et al 2006), books (Neville 1996;Taylor 1990), and Section 3.0 in the Cast Stone Phase II report (Sundaram et al 2011) provide more details on cement hydration processes and the underlying chemical and physical processes that give Cast Stone and Saltstone their desired properties. These resources can be read to gain a deeper understanding.…”
Section: Waste Form Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several review articles (Mattus and Gilliam 1994;Langton et al 2001;Milestone et al 2006), books (Neville 1996;Taylor 1990), and Section 3.0 in the Cast Stone Phase II report (Sundaram et al 2011) provide more details on cement hydration processes and the underlying chemical and physical processes that give Cast Stone and Saltstone their desired properties. These resources can be read to gain a deeper understanding.…”
Section: Waste Form Descriptionmentioning
confidence: 99%
“…The oxide composition and some of the physical properties for the three major Cast Stone dry ingredients that were used by PNNL to solidify/stabilize secondary liquid waste during the Phase II activities (see Sundaram et al 2011) are shown in Table 2.1. The Portland cement and BFS were obtained from LaFarge North America, Inc. (closest office Pasco, Washington).…”
Section: Cast Stone Ingredientsmentioning
confidence: 99%
See 3 more Smart Citations